FACTORS THAT AFFECTING THE PHARMACY LOYALTY ON THE PHARMACEUTICAL WHOLESALER - Dianita Rifqia Putri; Suci Paramitasari Syahlani; Djoko Wahyono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The primary component for maintaining the long term sustainability of a company is customer loyalty. Many factorsaffect customer loyalty in the business-to-business relationship. This study aimed to determine the factors that affect the pharmacy loyalty to the pharmaceutical wholesaler.The study was obtained using questionnaire with 1-4 Likert scale. The sampling method was purposive sampling and the sample was 130 respondents. The questionnaire validaty was tested by factor analysis, while the reliability test was conducted usingCronbach’s Alpha. Data were analyzed using SEM-PLS (Structural Equation Modeling-Partial Least Square).The results showed that pharmaceutical wholesaler’s service quality had a positive effect on pharmacy satisfaction (p-value <0.001 and the path coefficient value = 0.566). Pharmacy satisfaction had a positive influence on pharmacy trust (p-value <0.001 andthe path coefficient value = 0.32), pharmacy commitment (p-value = 0.005 and the path coefficient value = 0.191), and pharmacyloyalty (p-value = 0.014 and the path coefficient value = 0.161). Pharmacy trust had a positiveinfluence on commitment pharmacy (p-value is 0.037 and the path coefficient value = 0.13) and a pharmacy loyalty toward the pharmaceutical wholesaler(p-value = 0.001 and the path coefficient value = 0.254). Commitment pharmacies had a positive effect on pharmacy loyalty (p-value= 0.034 and the path coefficient value = 0.134). To sum up, the most powerful factor among the three variables in influencingloyalty was pharmacy trust.Keywords: service quality, satisfaction, trust, commitment, loyalty